Assessing Anthropometric Failure in Region Affected by High Stunting Prevalence - Hasna Izdihar Latifah; Suyatno; Alfi Fairuz Asna (Universitas Airlangga, 2026)
The Extended Composite Index of Anthropometric Failure (ECIAF) indicator is one of the best choices to identify malnutrition and describe nutritional problems broader. Nevertheless, it has not been widely used in most countries, such as Indonesia, which currently experiencing double-burden malnutrition. This study seeks to investigate child malnutrition status based on ECIAF in areas with very high stunting prevalence in Indonesia. This research utilized a cross-sectional approach, utilizing data collected from the 2022 Indonesian Nutrition Status Survey (SSGI). Study population consisted of children in West Sulawesi Province aged between 0 and 23 months. Following their exclusion for incomplete data and outlier analyses, 1,573 of 1,327 eligible participants made it into final analysis. Analysis employed logistic regression, adjusting for complex survey design. According to ECIAF classification, 25.7% of children under five experienced growth disorders. Multivariate analysis revealed that growth failure was significantly associated with being aged between 0 and 23 months (OR=3.8; CI: 2.09–7.05; p<0.001), male gender (OR=1.6; CI: 1.18–2.24; p=0.003), low birth weight (<2500 g) (OR=6.6; CI: 3.74–11.54; p<0.001), and incomplete vaccination (OR=1.7; CI: 1.22–2.46; p=0.002).The utilization of ECIAF to assess child malnutrition revealed a prevalence reaching a quarter of the entire child population. The risk factors of child malnutrition based on ECIAF in regions with high stunting prevalence were older child age, male gender, low birth weight, and not fully immunized.